Analysis of Digital Marketing Adoption Behaviour in MSMEs in Bengkulu City using the UTAUT-3 Model - Renaningtias, Nurul; Hidayat, Pradifta Irsyad; Erlansari, S.T.,M.Eng, Aan (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
Micro, Small and Medium Enterprises (MSMEs) are business groups engaged in the economy and are the largest economic actors in Indonesia that support the increase in Indonesia's economic income, Based on the latest data from the Cooperatives and SMEs Office of Bengkulu City in 2019 stated that the total MSMEs in Bengkulu City amounted to 45,702 MSMEs. This study aims to analyze the behavior of digital marketing adoption in MSMEs in Bengkulu City with the aim of finding factors that influence digital marketing adoption behavior in MSME actors and how MSME actors behave towards digital marketing adoption. This research is a quantitative research using the Unified Theory of Acceptance and Use of Technology-3 (UTAUT-3) Model. Data collection was carried out in this study by distributing questionnaires to 100 respondents of MSME actors. Data analysis performed using SmartPLS 4 software. The results of this study show that Performance Expectancy, Social Influence, Hedonic Motivation influence the behavioral intention of using digital marketing in MSME actors in Bengkulu City. Performance Expectancy has the strongest influence with a path coefficient value of 0.481 which means MSME players adopt digital marketing because it can develop their business, help promotion, increase productivity, and increase business sales. While Habit and Behavioural Intention can directly affect the behavior of using digital marketing in MSME actors. It is known that the most widely used digital marketing platform is WhatsApp with 94% of users, the social environment has proven to be more influential than innovation from within MSME actors in adopting digital marketing.